Graduating from high school overseas and Academic Transition to Indonesian University Atmosphere - Wahyuni, Nurul; Mirizon, Soni; Silvhiany, Sary (Universitas Jambi, Indonesia, 2023)
This research aimed to explore the academic transition of Indonesian university students who graduated high school overseas from Qatar to Indonesia, specifically speaking about their experiences and challenges in the academic transition. The research implemented a qualitative design with a narrative approach to get in-depth information on the lives of everyone. This research involved 5 Indonesian university students who had stayed ten years or more in Qatar and studied in Indonesia. The data were collected through a semi-structured interview and documents of reflective writing as supporting data. The data were analyzed by using thematic analysis. The findings revealed that due to the academic transitions from one country to their homeland, the transition was difficult when comparing both education systems in Qatar and Indonesia. Furthermore, no additional classes, or orientation programs were effective in preventing the challenges they faced. The challenges were emotional anxiety, loss of the English language, and peer pressure. Fortunately, this transition phase was not static and could be fixed.